Penerapan Pembelajaran Kooperatif Tipe Think Pair Share (TPS) untuk Meningkatkan Aktifitas dan Hasil Belajar - Mustamin, Kaso (Lembaga Yasin AlSys, 2024)
This research is a classroom action research, which was conducted in 2 cycles. The subjects of this study were X2 class students of SMA Negeri 3 Barru, totaling 30 people. The research was conducted in the even semester of the 2022/2023 academic year. This study aims to determine the improvement of learning quality in the form of increased learning activities and biology learning outcomes through the application of Think Pair share (TPS) type cooperative learning. The results showed that the application of cooperative learning type Think Pair share (TPS). can improve the quality of learning in the form of activities and learning outcomes of biology. Student learning activities were measured using activity observation sheets with an average percentage value of 81.33% in cycle I increasing to 98.00% in cycle II or increasing by 16.67%. %. Biology learning outcomes of students as measured by the average score obtained and the percentage of student learning achievement, which is based on the KKTP value of 80. In cycle I the average score was 81.43 and the level of student learning achievement was 73.33% and in cycle II the average score increased to 87.50 or an increase of 6.07 and student learning achievement increased to 100% of students achieved their learning objectives or an increase of 26.67%.